NK cell function down regulated by HMGB2 through ANGPT1/PI3K/AKT pathway and its effect on esophageal squamous carcinoma cells - Yin, Xiaodi; Cai, Huihong; Zhang, Aohua; Zheng, Weihan; Zhao, Jiahui; Ma, Jun (Frontiers in Immunology, 2025)
Natural killer (NK) cells are crucial for immune defense against tumors, but their function is often impaired in the tumor microenvironment. High mobility group box 2 (HMGB2), a chromatin-associated protein, is implicated in various cancers, yet its role in regulating NK cells, particularly in esophageal squamous cell carcinoma (ESCC), is unclear. We conducted transcriptomic and proteomic analyses of peripheral blood mononuclear cells (PBMCs) from ESCC patients and healthy donors to identify immunoregulatory molecules. Flow cytometry confirmed upregulation of HMGB2 in NK cells from ESCC patients, correlating with advanced tumor stage. Using RNA interference, CRISPR/Cas9, and overexpression methods, we modulated HMGB2 in NK-92 cells and assessed their cytotoxicity against ESCC cells. HMGB2 silencing or knockout enhanced NK cell cytotoxicity, evidenced by increased granzyme B, perforin, IFN-γ, and TNF-α, and higher tumor cell lysis. Conversely, HMGB2 overexpression suppressed these effects. Mechanistically, HMGB2 ablation induced ANGPT1 expression and activated the PI3K/AKT pathway. ANGPT1 knockdown in KO-HMGB2 NK cells reduced PI3K/AKT activation, confirming the involvement of the ANGPT1/PI3K/AKT axis in enhanced NK cell function. These results indicate that HMGB2 inhibits NK cell-mediated anti-tumor immunity in ESCC. HMGB2 depletion enhances NK cell cytotoxicity via the ANGPT1/PI3K/AKT pathway, suggesting its potential as a therapeutic target to improve NK cell-based immunotherapy in ESCC.